FACTORS RELATED TO MUSCULOSKELETAL DISORDER COMPLAINTS IN HIFTING WORKERSIN THE BULOG WAREHOUSE JAMBI - yenni, melda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
In indonesia, there are still some companies that do the work manually. One of these companies that still do the work of lifting-transport manually i.e. Public Company or Logistics Agency bulog perum. Transport workers is one part of the community workers need to get attention because the work they do much to contain risks to health. one of the complaints frequently suffered by transport-lifting is a musculoskeletal disorderThis research was carried out in the Regional divisions of the Bulog Jambi on musculoskeletal keluhuan. Determination of the sample of this research as many as 43 people.  The population of this research is all workers lift-angkt in the Regional divisions of the Bulog Jambi. Design research is a cross sectional sample is selected by the total sampling techniques. Data retrieval is performed using a questionnaire and analyzed with pulse measurement using univariate analysis and bivariat.The results of the statistical analysis using chi-square shows there is a connection between the long work with a value of p = 0.004, and workload with p = 0000 complaints of musculoskeletal disorder on lift-transport workers in methods of manual handling in the warehouse Bulog Regional Division of Jambi Should use the workload that is not too heavy in preventing musculoskeletal complaints, work in accordance with the procedure and does not use the working hours can be risky for health.